PERANAN MAJELIS PENGAWAS NOTARIS WILAYAH PROVINSI JAMBI DALAM MELAKUKAN PENGAWASAN TERHADAP PARA NOTARIS YANG BERKEDUDUKAN DI KABUPATEN BUNGO - , Triyoga ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is a research-juridical law that aims to determine the empirical form of supervision and guidance by the Supervisory Council of the Territory of Jambi Province Notary based in Bungo District as well as factors that become obstacles in conducting surveillance and guidance to the Notary based in Bungo Regency. The study was based on field research in order to obtain primary data and also do library research to obtain secondary data. The sampling technique used in this study was purposive sampling techniques Sampling is done with certain criteria armed with enough knowledge about the population to elect members of the sample. As for the sample in this research that the notary who is domiciled in the district of Bungo, and Members of the Supervisory Council of Jambi Province Region. Notary Public based in Bungo Regency currently directly supervised and trained by the Supervisory Board has not formed due to the Regional Assembly Regional Supervisor in the District of Bungo. Supervision and guidance by the Supervisory Council District so far are in accordance with the provisions of the Act and regulations. In carrying out supervision and guidance is found by Notary based in Bungo District has a good compliance rate, even one of them was awarded a certificate of Notary predicated either provided by the Council through the Central Supervisory Board Supervisory District. From the research found the constraints of the inadequate provision of funds and a considerable distance, but try to overcome these obstacles by making arrangements well in advance of conducting surveillance.